Teleost fish IgM+ plasma-like cells possess IgM-secreting, phagocytic, and antigen-presenting capacities - Wu, Liting; Yang, Yanjian; Gao, Along; Li, Jun; Ye, Jianmin (Frontiers in Immunology, 2022)
Plasma cells are terminally differentiated antibody-secreting B lymphocytes that contribute to humoral immunity by producing large numbers of antibodies. Increasing evidence suggests that teleost fish B cells share certain characteristics with mammalian B1 B cells, including antibody-secreting, phagocytic, and antigen-presenting capacities. However, the difference between mature B cells and plasma cells remains unclear. In this study, we found that, based on their light-scattering characteristics, tilapia anterior kidney (AK) leukocytes can be categorized into two IgM+ B-cell subsets: the lymphoid (L) gate and granulocyte–monocyte/macrophage (G-M) subsets. G-M gate cells are more numerous than L-gate cells and have higher mean fluorescence, but lower forward scatter and side scatter. We analyzed the morphological and ultrastructural features of sorted IgM+ cells and found that L-gate IgM+ cells have a high nucleus–cytoplasm ratio and lymphocyte-like morphology, whereas G-M gate IgM+ cells have a small nucleus, more abundant endoplasmic reticulum, and a larger number of mitochondria, and have a plasma cell-like or macrophage-like morphology. To further characterize the cell types, we examined the specific patterns of expression of B-cell- and T-cell-related genes. We found that B-cell-specific genes were expressed by both L-gate and G-M gate IgM+ cells, and that G-M gate IgM+ cells secreted extremely high levels of IgM. However, T-cell-related genes were highly expressed only in L-gate IgM– cells. These results suggest that G-M gate IgM+ cells are similar to plasma-like cells, with high antibody-secreting capacity. Given that G-M gate cells include the granulocyte, monocyte, and macrophage cell types, but not B cells, monocyte/macrophage markers were used to investigate the cell types further. A macrophage receptor with a collagenous structure was frequently observed, and macrophage-expressed gene-1 was highly expressed, in the G-M gate IgM+ cells. Phagocytic capacity, as determined by ingestion of beads or bacteria, was significantly higher in G-M gate IgM+ cells than in L-gate IgM+ cells, as was antigen-processing capacity. Our findings show that tilapia AK leukocytes can be divided into two IgM+ B-cell subsets and that G-M gate IgM+ cells resemble plasma-like cells, having high antibody-secreting, phagocytic, and antigen-presenting capacities. Thus, this study increases our understanding of the functions of teleost fish plasma-like cells.